2021
DOI: 10.3389/fcell.2020.618157
|View full text |Cite
|
Sign up to set email alerts
|

Sensing R-Loop-Associated DNA Damage to Safeguard Genome Stability

Abstract: DNA transcription and replication are two essential physiological processes that can turn into a threat for genome integrity when they compete for the same DNA substrate. During transcription, the nascent RNA strongly binds the template DNA strand, leading to the formation of a peculiar RNA–DNA hybrid structure that displaces the non-template single-stranded DNA. This three-stranded nucleic acid transition is called R-loop. Although a programed formation of R-loops plays important physiological functions, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 123 publications
(158 reference statements)
0
36
1
Order By: Relevance
“…The interplay of splicing factors and RNA-binding proteins (RBPs) are found to play an important role in DNA-RNA hybrid (R-loop) formation during transcription to prevent RNA-induced genome instability [59]. In cancers, mutations in the spliceosome machinery can affect R-loop formation, promoting genomic instability [60][61][62].…”
Section: Mechanisms Of Formation Of Chimeric Rnas In Cancer Cells and Their Functional Associations With Cancer Developmentmentioning
confidence: 99%
“…The interplay of splicing factors and RNA-binding proteins (RBPs) are found to play an important role in DNA-RNA hybrid (R-loop) formation during transcription to prevent RNA-induced genome instability [59]. In cancers, mutations in the spliceosome machinery can affect R-loop formation, promoting genomic instability [60][61][62].…”
Section: Mechanisms Of Formation Of Chimeric Rnas In Cancer Cells and Their Functional Associations With Cancer Developmentmentioning
confidence: 99%
“…While both drugs are topoisomerase II inhibitors, etoposide forms topoisomerase poisoning complexes, blocking DNA resealing during the enzymatic reaction, whereas doxorubicin intercalates into the double helix compromising topoisomerase functions, RNA-and DNA synthesis as well as generating free oxygen radicals (38,39). Therefore, etoposide primarily induces DSBs, while doxorubicin additionally causes formation of oxidative DNA lesions, DNA adducts and RNA-DNA hybrids, representing obstacles for nascent DNA synthesis (74). Interestingly, when we studied MLLbcr rearrangements following a short (4 h) treatment period and a long (72 h) recovery period versus uninterrupted treatment, a recovery period was necessary to unveil the protective effect of Fa27 during doxorubicin but not etoposide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is further confirmed by the accumulation of R-loops in mitotic germ cells of the testis in mice deleted for Atm or Tdp1, two DNA-damage response genes required for repair of DNA breaks [ 136 , 137 , 138 ]. In this regard, it has been also demonstrated that defects in the homologous recombination (HR) proteins BRCA1 and BRCA2 [ 139 , 140 ], in the nucleotide excision repair (NER) proteins XPG and XPF [ 141 ] and in the Fanconi anemia (FA) pathway [ 142 , 143 , 144 ], lead to R-loop accumulation, thus indicating that several DNA repair pathways contribute to R-loop regulation [ 145 ].…”
Section: Rna Splicingmentioning
confidence: 99%